The Influence of Self Control and Economic Literacy on Student Lifestyle (at Madrasah Aliyah Islamiyah Ciputat) - Yuangga, Kharisma Danang; Jasmani, Jasmani (Universitas Negeri Makassar, 2018)
Consumptive behavior carried out at adolescence is more likely to be impulsive and sudden. The purpose of this study was to determine the effect of self-control and economic literacy on students' lifestyles on the MA Islamiyah Ciputat. The method used is descriptive method with an associative approach. The sampling technique used was proportional random sampling using a sample of 75 respondents. The analysis tool uses validity test, reliability test, classic assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are self-control and a significant positive effect on student lifestyle by 40.7%. Hypothesis testing is obtained tcount> ttable or (7.082> 1.993), so that H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between self-control of students' lifestyles at the Ciputat MA Islamic Office. Economic literacy has a positive and significant effect on student lifestyle by 36.2%. Hypothesis testing is obtained tcount> ttable or (6.438> 1.993) so that H0 is rejected and H2 is accepted meaning that there is a positive and significant influence between economic literacy on students' lifestyles. A simultaneous test of self-control and economic literacy has a positive and significant effect on students' lifestyles with a contribution of 48.4%, while the remaining 50.3% is influenced by other factors. Hypothesis testing obtained the value of Fcount> Ftable or (36.384> 2.730), thus Ho is rejected and H3 is accepted. This means that there is a positive and significant effect simultaneously between self-control and economic literacy on the lifestyle of students at MA Islamiyah Ciputat.